Differences Ratio Level Soluble FMS-Like Tyrosine Kinase-1 and Placental Growth Factor Early And Late Onset on Preeclampsia and Normal Pregnancy - Ria Andina; Yanwirasti Yanwirasti; Defrin Defrin (Journal of Midwifery, 2018)
Preeclampsia is a major maternal morbidity and mortality worldwide including in Indonesia. PIGF concentrations were found to be lower and sFlt-1 to be higher in patients with preeclampsia than normal pregnancy. Futher, this factor has been proposed as a parameter that can help identify women with potentially preeclampsia.This study aims todeterminethe differences ratio level soluble rate fms-like tyrosine kinase-1 and placental growth factor early and late onset on preeclampsia and normal pregnancy. The cross sectional study design was conducted in RSUP M.Djamil, Rasidin Hospital, Reksodiwiryo Hospital and Biomedical Laboratory of Andalas University from July 2017 until January 2018. The sample of this study was pregnant women>20-42 weeks pregnancy totalling 80 people by consecutive sampling.Sample was divided into 3 groups. SFlt-1 and PlGF levels tested using ELISA test. Test the normality of data by Kolmogrov-Smirnov test by using unpaired T test.The results showed median sFLT-1 levels in the early onset group with normal pregnancy with p= 0,88, median sFLT-1 levels in the late onset group with normal pregnancy with p= 0,01 and median levels of sFLT-1 in the early onset group with late onset with p= 0.34. Mean of PlGF in the early onset group with normal pregnancy with p=0,30, mean of PlGF in the late onset group with normal pregnancy with p= 0.63, and mean of PlGF in the early onset group with late onset with p = 0.27. The conclusion of this study was that there was a difference ratio level Soluble Fms-Like Tyrosine Kinase-1 late onset in preeclampsia and normal pregnancy.